(untitled) (Communication & Society, 2018)
Fact-checking has experienced substantial growth in recent years, as a technique aimed to monitor public discourse, at a time when the dissemination of fake news or the loss of media quality and credibility has reached worrying levels. This article analyzes nine projects launched since 2010 in half a dozen Latin American countries, representative of an emerging ecosystem in a region facing problems to achieve genuine media democracy. From a qualitative and quantitative approach, this research compares the work methodology and the evaluation models presented by the digital platforms, as well as the topics and actors that are subject to examination. The study highlights the aim of these projects, independent of traditional media, to evaluate statements on the most relevant issues of the sociopolitical agenda of their countries and public representatives. The importance of these platforms is reflected in the fact that only two in ten checks from the sample can be considered true, almost half of those identified as false and of those presenting some kind of inaccuracy. The analysis reveals significant differences when carrying out the verifications and presenting the results, with options for improvement in the number of sources, the inclusion of expert voices and audiovisual resources, or the interaction with readers. The Argentinian platform Chequeado appears as a reference model in this context.